Real-Time MRI Monitoring of GelMA-Based Hydrogel-Loaded Kartogenin for In Situ Cartilage Regeneration - Zhang, Hanyuan; Fang, Weijun; Zhao, Tingting; Zhang, Huabing; Gao, Liang; Li, Jingya; Wang, Rujing; Xu, Weiping (Frontiers in Bioengineering and Biotechnology, 2022)
The cartilage has poor ability to mount a sufficient healing response. Herein, kartogenin (KGN), an emerging stable non-protein compound with the ability to recruit bone marrow mesenchyme stem cells (BMSCs) to promote chondrogenic differentiation, was grafted onto dopamine-Fe(III) chelating nanoparticles, followed by involving a gelatin- and dextran-based injectable hydrogel to mimic the extracellular matrix to promote cartilage repair. The in vitro results demonstrated that KGN underwent long-term sustained release behavior and availably promoted the deep migration of BMSC cells in yielding hydrogels. Furthermore, in vivo New Zealand white rabbits’ cartilage defect model repairing results showed that cartilage defect obtained significant regeneration post operation in the 12th week, and the defect edge almost disappeared compared to adjacent normal cartilage tissue. Meanwhile, the T2-weighted magnetic resonance imaging (MRI) property resulting from dissociative Fe (III) can significantly monitor the degradation degree of the implanted hydrogels in the defect site. This integrated diagnosis and treatment system gives insight into cartilage regeneration.